2008
DOI: 10.1590/s1415-790x2008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da fauna de triatomíneos e da ocorrência de doença de Chagas em Monte Negro, Rondônia, Brasil

Abstract: A doença de Chagas tem como agente etiológico o Trypanossoma cruzi, um protozoário flagelado que pode ser encontrado numa grande variedade de mamíferos e triatomíneos. O Estado de Rondônia, localizado na Amazônia Ocidental, possui um meio ambiente constantemente modificado pelas ações transformadoras do ser humano, resultando em um desequilíbrio, que pode facilitar a transmissão de inúmeros patógenos. Uma grande variedade e quantidade de palmáceas, em especial o babaçu, bem como mamíferos e triatomíneos, podem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
5
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 16 publications
1
26
5
16
Order By: Relevance
“…Such a correlation was also noticed by Massaro et al 9 in studies previously carried out in the same region (Monte Negro). The short time that the area has been populated by humans may be the reason why the vector has not yet settled around it.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Such a correlation was also noticed by Massaro et al 9 in studies previously carried out in the same region (Monte Negro). The short time that the area has been populated by humans may be the reason why the vector has not yet settled around it.…”
Section: Discussionsupporting
confidence: 83%
“…In their study, also carried out in Monte Negro, Massaro et al 9 found the existence of the species R. robustus, R. pictipes, R. prolixus, R. milese, and Panstrongylus geniculatus; the latter being found during soaring and intradomiciliarily (dormitory). It is possible that the existing difference between the results found in this study from the study carried out by Massaro et al 9 is the non-random characteristic of their samples and because the samples were obtained in a limited area (10 sites) and in the surrounds of urban areas 9 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations